Computational study of FaEXPA1, a strawberry alpha expansin protein, through molecular modeling and molecular dynamics simulation studies. (October 2018) - Valenzuela-Riffo, Felipe; Ramos, Patricio; Morales-Quintana, Luis
Graphical abstract: Highlights: Expansins are proteins associated to several processes, including fruit ripening. FaEXPA1 a α-expansins from strawberry was structurally characterized. The model displayed an open groove located at the central part of expansin. Protein-ligand interactions were evaluated with cellulose as ligand. Abstract: Changes in the cellulose-hemicellulose fraction take place during ripening of strawberry fruit and are associated with the activity of a set of proteins and hydrolytic enzymes. Expansins are proteins located in the cell wall with no catalytic activity. In this context, FaEXPA1 was previously reported to have a high accumulation rate during fruit ripening in three different strawberry cultivars. In order to understand at the molecular level the expansin mechanism mode, a 3D model of FaEXPA1 protein was built by comparative modeling. FaEXPA1 protein model displayed two domains, a cellulose-binding domain with a β-sandwich structure, and a second domain that included a HFD motif with a similar structure to the catalytic core of endoglucanase V from Humicola insolens . Additionally, in the center of the structure, an open groove was formed. Finally, using a cellulose polymer as a ligand, the protein-ligand interaction was evaluated by molecular dynamic (MD) simulation. Two MD simulations showed that FaEXPA1 can interact with cellulose via the flat aromatic surface of its binding domain D2, composed mainly of residues Trp99 and Trp225. In addition, FaEXPA1 formed a high number of hydrogen bonds with the glycan chain and the Asn81, Phe114 and Asn211 residues.